A Smart Tower Crane to Mitigate Turbulent Wind Loads. Issue 1 (2nd January 2021) - El Ouni, Mohamed Hechmi; Ben Kahla, Nabil; Islam, Saiful; Jameel, Mohammed
Abstract: Tower cranes have, in general, low structural damping, leading to challenges with respect to vibrations induced by natural hazards. Crane failures due to wind excitations are very common around the world. In the present research work, a smart tower crane equipped with pairs of collocated sensors and actuators is proposed to mitigate turbulent wind. A three-dimensional finite element model of the crane is created using MATLAB ® /Structural Dynamics Toolbox. Modal analysis is performed to calculate natural frequencies and corresponding mode shapes. Dynamic analysis of the crane is carried out under turbulent wind excitation. A decentralized active vibration control method is then used to prevent collapse of the crane. Active damping is added to the tower crane using pairs of force actuators–displacement sensors collocated on selected elements. A robust control strategy based on decentralized direct velocity feedback is implemented. The vibrations of the tower crane in all directions are significantly damped. It is concluded that the proposed smart tower crane model is highly efficient in mitigating the turbulent wind loads.